Inter-Environmental Collaboration to Form Students’ Attitudes toward Diversity - Asiah, Nur; Harjoni, Harjoni; Susanto, Is (Universitas Islam Negeri Raden Intan Lampung, 2021)
An excellent religious attitude can direct students to think and act following the religious values they adhere to in their personal and social lives. This study aimed to analyze the environmental factors in the formation of students' attitudes toward diversity. This study used a qualitative method. The data had been obtained from all informants at SDIT Muhammadiyah, SD Trihasil, and MI Nahdlatul Ulama that met the specified requirements. The data had been collected through interviews, observation, and documentation techniques to be analyzed descriptively. The results showed that the factors forming students' attitudes toward diversity were the family environment, school environment, and community environment. For example, factors that formed the religious attitude of SD Trihasil students were religious education and the family environment. The parents provided religious education through daily habituation and invited their children to daily and monthly recitation. On the other hand, factors that formed students' attitudes toward diversity at SDIT Muhammadiyah were the family through habituation and the Muhammadiyah organization. Furthermore, students’ attitudes toward diversity MI Nahdatul Ulama were influenced by family factors and their community. Thus, internal and external environmental factors influence the students’ attitudes toward diversity.